Analisis Implementasi Program Thematic Education Outlet Sebagai Strategi Penguatan Branding Perbankan - Prasetian Dewi, Arlinta (At-Tasyri: Jurnal Hukum Islam dan Ekonomi Syariah, 2025)
This research aims to analyze the extent of success of the thematic education outlet program launched by BNI. The method used is qualitative descriptive by collaborating case studies and literature review. The data obtained will be analyzed in such a way as to produce a conclusion. The research results show that the thematic education outlet program is able to provide a customer experience to encourage the migration of customer transactions towards digital. This program provides a faster, more informative and complete experience as well as easy and comfortable operational access for customers. The concept and services of this program are ultimately effective in encouraging BNI’s rebranding to become a millennial and more digital bank as well as supporting the development of international banking services